Kekerasan Fisik Yang Dilakukan Oleh Anggota Polri Terhadap Masyarakat - Siahaya, Josua Valen; Lewerissa, Yanti Amelia; Patty, Jetty Martje (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: The National Police is a public security protection agency, but now many individuals are caught committing acts that disrupt security and even persecute the community. The existence of these violations adds to the long blacklist of increased violations of discipline and code of ethics committed by members of the National Police.Purposes of the Research: To analyze physical violence committed by members of the National Police against the community, this is because the police is a subsystem that is directly related to the perpetrators of crimes and the community, so that the duties and responsibilities of the police can be said to be greater than other subsystems.Methods of the Research: The method used to analyze and discuss this problem is Normative Juridical.Results of the Research: Increased police commitment to better protection and promotion of human rights at the national level. This was realized by the birth of Law No. 39 of 1999 concerning Human Rights. As stipulated in international human rights law and standards, the police have rights, but there are also limits to the powers of the police. However, different from the expected reality, the presence of the police in the midst of the community has caused a scourge for the community. There is police behavior that deviates from the expected professional ethics and there are also those that make the community miserable, such as pungli, arrogant and violent behavior. This causes a fall in public trust in the police Regardless of whether the actions of the National Police are true or not, in the institution of the National Police if there are irregularities, violations of the law and abuse of authority, then members of the National Police will be processed based on the applicable rules.